A 50‐Year Tropical Cyclone Exposure Climatology in Southeast Asia. Issue 4 (15th February 2022) - Tran, Thao Linh; Ritchie, Elizabeth A.; Perkins‐Kirkpatrick, Sarah E.
Abstract: In this study, the landfalling tropical cyclone (TC) exposure in Southeast Asia for a 50‐year period from 1970 to 2019 is investigated relative to the total western North Pacific (WNP) climatology taking disparities in historical records into account. Long‐term trends in landfalling TCs are analyzed and intercompared among the Regional Specialized Meteorological Center of Tokyo (TOKYO), China Meteorological Administration (CMA), Hong Kong Observatory (HKO), and Joint Typhoon Warning Center (JTWC) best track datasets. Interannual and intra‐seasonal variations are further examined by sub‐region and nation using JTWC records. Approximately half of the WNP TCs make landfall in Southeast Asia representing over 75% of the total WNP landfalls in all datasets. Over the study period, there is a slight upward trend in landfalling TC frequency in both the WNP and Southeast Asia in the JTWC dataset, while the number of landfall events has decreased in the CMA and TOKYO datasets. A consistent northward shift in landfalling locations over the 50‐year period is found in all datasets such that landfalls have decreased in the Philippines, Vietnam, but increased in some South China areas. The TOKYO dataset alone suggests that landfalling TCs in South China have slowed down over the study period, which would increase rainfall and wind risks in their path if substantiated. Less TC landfalls occur in El Niño years with landfalling locations shifting northwestward over the Asian mainland, while landfalls are higher and more distributed in La Niña, and highest in Neutral years. Key Points: Approximately half of all Western North Pacific tropical cyclones made landfall in Southeast Asia A northward shift of landfalling locations is found in all four agency best track records Landfalls are lower and shifted northwestward in El Niño, higher and more distributed in La Niña, and highest in Neutral years